2021
DOI: 10.1038/s41598-021-00514-0
|View full text |Cite
|
Sign up to set email alerts
|

Microclimate and the vertical stratification of potential bridge vectors of mosquito‑borne viruses captured by nets and ovitraps in a central Amazonian forest bordering Manaus, Brazil

Abstract: In the Americas, some mosquito-borne viruses such as Zika, chikungunya, and dengue circulate among humans in urban transmission cycles, while others, including yellow fever and Mayaro, circulate among monkeys in sylvatic cycles. The intersection of humans and wildlife at forest edges creates risk for zoonotic virus exchange. We built a scaffold tower at the edge of a treefall gap in rainforest bordering Manaus, Brazil, to identify vectors that may bridge transmission between humans and monkeys. We vertically s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 46 publications
2
24
1
Order By: Relevance
“…This result differs from several studies in which the species is cited as an acrodendrophile [45,53,55,65,66]. On the other hand, it adds to the results of other studies where variations in this pattern were observed [3,44,56].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This result differs from several studies in which the species is cited as an acrodendrophile [45,53,55,65,66]. On the other hand, it adds to the results of other studies where variations in this pattern were observed [3,44,56].…”
Section: Discussioncontrasting
confidence: 99%
“…However, in both studies, the hand-net was the technique with greater richness and diversity and lower dominance in both strata, while the indicators of traps using only BG-Lure® demonstrated inefficiency, a result also found for wild diurnal mosquitoes in Brazil by other researchers [55,56]. This shows that the exclusive use of BG-Lure® may be inefficient for wild neotropical species.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Host-seeking female Haemagogus species mosquitoes were collected at the Adolpho Ducke forest reserve bordering Manaus in the Brazilian Amazon between February and April 2022. Approaching mosquitoes were collected with handheld nets at ground level and on elevated platforms during the daytime (10:00–15:00) at a treefall (02.92537° S, 059.96582° W) [ 36 ]. Captured mosquitoes were transferred to a 16 × 19.5 cm cylindrical cardboard cage and provided with cotton wool soaked with mineral water for hydration.…”
Section: Methodsmentioning
confidence: 99%
“…Field collected mosquitoes were sampled at a site where >97% of anthropophilic Haemagogus were known to be Hg. janthinomys [ 36 ]. All individually maintained mosquitoes (field collected and F 2 adult females) were morphologically identified using a stereomicroscope and relevant taxonomic keys [ 2 , 37 , 38 , 39 ].…”
Section: Methodsmentioning
confidence: 99%